A praça dos trabalhadores de Guaianazes: periferia de São Paulo - Castilho, Edimilsom Peres (2007)
This research intends to understand the social and historical constitution of the squares in our cities as a category of urban landscape, using as basis to this study the analysis of the social appropriation of the square in Guaianases, in the suburbs of São Paulo. The Guaianases square, which from the year 2001 to 2003 went through a remodeling process through an Urban Interventions Municipal Program called Urban Centralities, presents an unique appropriation manner which reveals a social logic that is a result of the conditions of the subjects that use the square. Therefore, apart from only describing the multiple ways of using the open urban areas in the suburbs of São Paulo, in this study we tried to learn about the social appropriation of this square according to the main determiners that reproduce the urban landscape in which it is in, respecting the process of social and historical constitution. This way, we tried to show that the social function of the Guaianases square is a product of the production and appropriation of the material lives of the people of that neighborhood, which makes it an important object for studies in order to understand the unique way that these particular individuals socialize